2022
DOI: 10.3390/polym15010135
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Optimization Studies of Polycaprolactone/Polylactic Acid/Titanium Dioxide Nanoparticle/Orange Essential Oil Membranes for Biomedical Applications

Abstract: The development of scaffolds for cell regeneration has increased because they must have adequate biocompatibility and mechanical properties to be applied in tissue engineering. In this sense, incorporating nanofillers or essential oils has allowed new architectures to promote cell proliferation and regeneration of new tissue. With this goal, we prepared four membranes based on polylactic acid (PLA), polycaprolactone (PCL), titanium dioxide nanoparticles (TiO2-NPs), and orange essential oil (OEO) by the drop-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Polycaprolactone is an important polymer in scaffolds, and the ability to produce composites increases its importance in this field [ 16 ]. Branched varieties, as well as PCL, have been extensively studied, which contain additional structural units such as glycidol, lactide, pentaerythritol or poly(ethylene glycol) [ 13 , 17 , 18 , 19 ]. However, only few studies to date have shown interest in highly branched PCL obtained by chain growth from a HP core.…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone is an important polymer in scaffolds, and the ability to produce composites increases its importance in this field [ 16 ]. Branched varieties, as well as PCL, have been extensively studied, which contain additional structural units such as glycidol, lactide, pentaerythritol or poly(ethylene glycol) [ 13 , 17 , 18 , 19 ]. However, only few studies to date have shown interest in highly branched PCL obtained by chain growth from a HP core.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, significant benefits have also been reported in the design of nanocomposite scaffolds incorporating essential oils, such as a higher rate of degradation, greater porosity and biocompatibility, and lower inflammatory response [22,23]. Essential oils are complex, odorous liquid mixtures of highly volatile compounds obtained from the secondary metabolism of plants by solvent extraction or hydrodistillation, with excellent anti-inflammatory, antimicrobial, antiviral, and therapeutic properties [24].…”
Section: Introductionmentioning
confidence: 99%